Portfolio Rebalancing - Qian, Edward E. (Boca Raton, FL : CRC Press, 2017)
"The goal of this book is to provide mathematical and empirical analysis of the effects of portfolio rebalancing on portfolio returns and risks. The mathematical analysis answers the question of when and why fixed-weight portfolios might outperform buy-and-hold portfolios. The empirical analysis, aided by mathematical insights, will examine the effects of portfolio rebalancing in capital markets and understand why many capitalization-weighted indices underperform fixed-weight portfolios."--Provided by publisher.
6.2 The Impact of Cross-Sectional Serial Correlations on Return Effect6.3 Approximating Return Effects of Long-Short Portfolios; 6.3.1 Two-Asset Long-Short Portfolios; 6.3.2 General Long-Short Portfolios; Problems; Chapter 7 Analysis of Rebalancing Alpha; 7.1 Rebalancing Alpha of Two-Asset Portfolios; 7.1.1 Pairwise t-Statistics; 7.1.2 Probability of Positive Rebalancing Alpha; 7.1.3 Expected Value and Standard Deviation of Rebalancing Alpha; 7.1.4 Distribution of Rebalancing Alpha; 7.2 Rebalancing Alpha of General Portfolios; 7.2.1 Pairwise Decomposition of Rebalancing Alpha
OCLC-licensed vendor bibliographic record.
Keywords: Portfolio management -- Mathematical models; MATHEMATICS -- Probability & Statistics -- General; BUSINESS & ECONOMICS -- Finance